1995
DOI: 10.1016/0735-1097(94)00350-y
|View full text |Cite
|
Sign up to set email alerts
|

Rest—redistribution thallium-201 scintigraphy to determine myocardial viability early after myocardial infarction

Abstract: If confirmed by larger studies, early rest-redistribution thallium-201 imaging may be a useful technique for identifying residual viability after myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…27 LeFeuvre et al reported that the diagnostic accuracy of 201 Tl-SPECT in the detection of viable myocardium is similar to that of dobutamine echocardiography, 28 and others have found that patients with evidence of rest redistribution have better left ventricular wall motion and higher left ventricular ejection fractions than patients without this phenomenon. 29 In general, patients with DMD do not have a significant coronary artery disease, so we believe that the mechanisms underlying redistribution in DMD differ from those usually associated with this phenomenon. The distinctive features seen in areas of redistribution were edema formation in the intermuscular and perivascular spaces and the presence of cells with swollen and irregularly shaped nuclei; damage to the myocyte membrane may influence Tl transportation through the Na + /K + channel.…”
Section: Discussionmentioning
confidence: 99%
“…27 LeFeuvre et al reported that the diagnostic accuracy of 201 Tl-SPECT in the detection of viable myocardium is similar to that of dobutamine echocardiography, 28 and others have found that patients with evidence of rest redistribution have better left ventricular wall motion and higher left ventricular ejection fractions than patients without this phenomenon. 29 In general, patients with DMD do not have a significant coronary artery disease, so we believe that the mechanisms underlying redistribution in DMD differ from those usually associated with this phenomenon. The distinctive features seen in areas of redistribution were edema formation in the intermuscular and perivascular spaces and the presence of cells with swollen and irregularly shaped nuclei; damage to the myocyte membrane may influence Tl transportation through the Na + /K + channel.…”
Section: Discussionmentioning
confidence: 99%
“…MVI has the possibility of being a predictor for myocardial viability after reperfused AMI because 201 Tl uptake of 60% was previously reported to be optimal in the prediction of myocardial viability. 23,24 The MVI decreased not only in the infarcted segments but also in surrounding segments, especially in patients with LAD-related AMI (Fig. 6).…”
Section: Resultsmentioning
confidence: 94%
“…Several studies have evaluated the efficacy of rest-redistribution thallium-201 imaging 17) or the combination of resting BMIPP images and resting thallium-201 images 7,18) in predicting the outcome of myocardial regions after revascularization. Pierard, et al 19) and other investigators, 4) using low dose dobutamine stress echocardiography 3-12 days after myocardial infarction with follow-up evaluations to reassess ventricular function 4 weeks to 9 months later, demonstrated that overall, the sensitivity for detecting reversible regional dysfunction ranged from 66% to 86%, with the specificity ranging from 68% to 94% and accuracy averaging 71%.…”
Section: Discussionmentioning
confidence: 99%